A photoswitchable fluorescent protein for hours-time-lapse and sub-second-resolved super-resolution imaging. (22nd January 2021) - Wazawa, Tetsuichi; Noma, Ryohei; Uto, Shusaku; Sugiura, Kazunori; Washio, Takashi; Nagai, Takeharu
Abstract: Reversibly photoswitchable fluorescent proteins (RSFPs) are a class of fluorescent proteins whose fluorescence can be turned on and off by light irradiation. RSFPs have become essential tools for super-resolution (SR) imaging. Because most SR imaging techniques require high-power-density illumination, mitigating phototoxicity in cells due to intense light irradiation has been a challenge. Although we previously developed an RSFP named Kohinoor to achieve SR imaging with low phototoxicity, the photoproperties were insufficient to move a step further to explore the cellular dynamics by SR imaging. Here, we show an improved version of RSFP, Kohinoor2.0, which is suitable for SR imaging of cellular processes. Kohinoor2.0 shows a 2.6-fold higher fluorescence intensity, 2.5-fold faster chromophore maturation and 1.5-fold faster off-switching than Kohinoor. The analysis of the pH dependence of the visible absorption band revealed that Kohinoor2.0 and Kohinoor were in equilibria among multiple fluorescently bright and dark states, with the mutations introduced into Kohinoor2.0 bringing about a higher stabilization of the fluorescently bright states compared to Kohinoor. Using Kohinoor2.0 with our SR imaging technique, super-resolution polarization demodulation/on-state polarization angle narrowing, we conducted 4-h time-lapse SR imaging of an actin filament network in mammalian cells with a total acquisition time of 480 s without a noticeable indication of phototoxicity. Furthermore, we demonstrated the SR imaging of mitochondria dynamics at a time resolution of 0.5 s, in which the fusion and fission processes were clearly visualized. Thus, Kohinoor2.0 is shown to be an invaluable RSFP for the SR imaging of cellular dynamics.